Penerapan Strategi Pembelajaran Berdiferensiasi Untuk Meningkatkan Hasil Pembelajaran Bahasa Indonesia - Sari HS, Dyan Wulan; Mardiana, Mardiana; Wita, Nora; Meilani, Frisa; Rani, Dwi (Mutiara: Multidiciplinary Scientifict Journal, 2025)
The aim of this study was to determine the implementation of differentiated learning strategies to improve student learning outcomes. The research used an action research method, with procedures including planning, implementation of actions, observation, and reflection. The data analysis techniques used were quantitative and qualitative data. The analysis results showed: 1) The Pre-Cycle Test results indicated that out of 17 students, 7 students (41.18%) achieved the minimum mastery criteria (KKM), while 10 students (58.82%) did not; 2) The Pretest in Cycle I showed that 9 students (52.94%) were successful, while 8 students (47.06%) were not; 3) The Posttest in Cycle I indicated that 12 students (70.59%) were successful, while 5 students (29.41%) were not; 4) The Posttest in Cycle II showed that 15 students (88.23%) were successful, while 2 students (11.77%) were not. The discussion results in Cycle I showed that the percentage of student learning mastery was 70.59%, while in Cycle II it increased to 88.23%, indicating an improvement in learning outcomes by 17.64%, meaning that the minimum mastery criteria (KKM) was achieved in Cycle II.